2021
DOI: 10.22541/au.163421567.77547120/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telomeres positively correlate with pace-of-life and elongate with age in a wild mammal

Abstract: Understanding ageing and the diversity of life histories is a cornerstone in biology. Telomeres, the protecting caps of chromosomes, are thought to be involved in ageing, cancer risks and to modulate life-history strategies. They shorten with cell division and age in somatic tissues of most species, possibly limiting lifespan. The resource allocation trade-off hypothesis predicts that short telomeres have thus co-evolved with early reproduction, proactive behaviour and reduced lifespan, i.e. a fast Pace-of-Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In contrast to early research in humans and cancer models, where telomeres typically shorten with age as a result of the end replication problem and oxidative stress OPEN ACCESS EDITED BY James Harper, Sam Houston State University, United States (Harley et al, 1990;Blasco, 2007;Aubert, 2014), recent research has shown that in some organisms telomeres can lengthen as individuals become older and that telomeres can even have a complex and dynamic role in life histories (Monaghan and Ozanne, 2018;Marasco et al, 2022). Such findings of active telomere maintenance struggled to find traction initially but repeated examples across many taxa have led to a general acceptance that the process is not uncommon non-model species (Hoelzl et al, 2016b;Criscuolo et al, 2020;Panasiak et al, 2020;Tissier et al, 2022;Giroud et al, 2023). The underlying mechanisms for telomere repair, however, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to early research in humans and cancer models, where telomeres typically shorten with age as a result of the end replication problem and oxidative stress OPEN ACCESS EDITED BY James Harper, Sam Houston State University, United States (Harley et al, 1990;Blasco, 2007;Aubert, 2014), recent research has shown that in some organisms telomeres can lengthen as individuals become older and that telomeres can even have a complex and dynamic role in life histories (Monaghan and Ozanne, 2018;Marasco et al, 2022). Such findings of active telomere maintenance struggled to find traction initially but repeated examples across many taxa have led to a general acceptance that the process is not uncommon non-model species (Hoelzl et al, 2016b;Criscuolo et al, 2020;Panasiak et al, 2020;Tissier et al, 2022;Giroud et al, 2023). The underlying mechanisms for telomere repair, however, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…All hibernation periods are typified by periods of extreme reduction in metabolism and body temperature (torpor) interspersed with short bursts of euthermia where individuals return to normal metabolism and body temperature before returning into the torpor phase (Lyman et al, 1982;Carey et al, 2003;Heldmaier et al, 2004;Hoelzl et al, 2015). Telomere attrition across hibernation has been shown in both edible dormice (Glis glis) and garden dormice (E. quercinus) as well as in other hibernating rodents such as Columbian ground squirrels (Urocitellus columbianus), eastern chipmunks (Tamias striatus), and also in some bat species (Hoelzl et al, 2016b;Foley et al, 2018;Nowack et al, 2019;Giroud et al, 2022;Tissier et al, 2022;Viblanc et al, 2022). In garden dormice however, individuals were able to maintain or increase relative telomere length (RTL) during hibernation when provided with food ad libitum (Giroud et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation